Potential Changes of Water Spinach (Ipomoea aquatica Forsk) Root’s Cell Membrane as an Indicator of Environmental Pollution of Waste Water - Siti Jazimah Iswarin (Natural B, Journal of Health and Environmental Sciences, 2011)
This research is to study the potential change of water spinach root cell membrane using various concentration of Pb ions in 20, 40, 60, 80, and 100ppm using water which come from irrigating rice field at three locations. Pb ions in water and water spinach are specified by Atom Spectrophotometer Spectrophotometer. The membrane potential change is regression determined. From the graph it is shown that the percentage change in membrane potential increases by Pb concentration. At the edge of the rice field, potential of water changes about (18±2) %, at 25 m from the edge, potential changes about (6±4) %, at 50 m from the edge, potential changes about (38±12) %. From this data, Pb2+ is 35.8 ppm (first location), 0 ppm (second location), and 135.3 ppm (third location). Pb2+ concentration calculated using AAS are 0.045 ppm (first location), 0.010 ppm (second location), and 0.025 (third location). In water spinach there are: Pb2 + / ppm; 3.0; 0.9; 5.6. The membrane potential is affected by the ion solution. The higher the pollution, the higher the membrane potential will be. Increasing the type of substance also increases the membrane potential changes that are sensitive to Pb ions. Based on this case the potential change of cell membrane of root of water spinach can be used as an indicator of pollution.